Cephalometric evaluation of skeletal base relationship in patients with cleft lip and palate in a tertiary hospital in South India - Meguja K Johnson; Maria John Kuriakose; N K Sapna Varma; V V Ajith; Pramod Subash (Wolters Kluwer Medknow Publications, 2020)
Objective: The study is aimed at assessing the cephalometric characteristics and distribution of skeletal base patterns in patients with cleft lip and palate (CLP) in a cohort of patients reporting to a tertiary hospital in South India. Materials and Methods: A retrospective observational study was carried out on 44 consecutive patients with CLP and 43 age- and sex-matched control orthodontic patients. Linear and angular measurements were obtained from the digitally traced lateral cephalograms using Dolphin software, and the data were analyzed. Results: Patients with CLP exhibit reduction in maxillary as well as mandibular length. Maxilla and mandible are both retropositioned and retrognathic. However, the maxillomandibular relationship shows the prevalence of Class I skeletal pattern (47.73%). Conclusion: Patients with CLP demonstrated smaller, retrognathic and retropositioned jaws, however with Class I skeletal relationship. The present data would be beneficial in determining the orthodontic requirements of patients with cleft in South India.